2010
DOI: 10.1128/aac.00587-10
|View full text |Cite
|
Sign up to set email alerts
|

Azole Binding Properties of Candida albicans Sterol 14-α Demethylase (CaCYP51)

Abstract: Purified Candida albicans sterol 14-␣ demethylase (CaCYP51) bound the CYP51 substrates lanosterol and eburicol, producing type I binding spectra with K s values of 11 and 25 M, respectively, and a K m value of 6 M for lanosterol. Azole binding to CaCYP51 was "tight" with both the type II spectral intensity (⌬A max ) and the azole concentration required to obtain a half-⌬A max being proportional to the CaCYP51 concentration. Tight binding of fluconazole and itraconazole was confirmed by 50% inhibitory concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 59 publications
(68 reference statements)
4
106
1
Order By: Relevance
“…The modeling experiments suggested that lanosterol could fit into the active site, as supported by the type I binding spectra, but could not orientate viously calculated K s value of 11 M for eburicol binding to MgCYP51 by UV-visible spectroscopy (16) suggesting that the K m value is not solely dependent on the affinity of MgCYP51 for substrate. The MgCYP51 K m value for eburicol was comparable with that determined for human CYP51 of 30 M with lanosterol (30) but was 4-to 6-fold larger than K m values previously determined for C. albicans and S. cerevisiae CYP51 enzymes (15,31,32), suggesting a degree of variability with regard to substrate affinity among CYP51 enzymes.…”
Section: Discussionmentioning
confidence: 59%
“…The modeling experiments suggested that lanosterol could fit into the active site, as supported by the type I binding spectra, but could not orientate viously calculated K s value of 11 M for eburicol binding to MgCYP51 by UV-visible spectroscopy (16) suggesting that the K m value is not solely dependent on the affinity of MgCYP51 for substrate. The MgCYP51 K m value for eburicol was comparable with that determined for human CYP51 of 30 M with lanosterol (30) but was 4-to 6-fold larger than K m values previously determined for C. albicans and S. cerevisiae CYP51 enzymes (15,31,32), suggesting a degree of variability with regard to substrate affinity among CYP51 enzymes.…”
Section: Discussionmentioning
confidence: 59%
“…L-Histidine was removed from the preparation by washing the enzyme with affinity chromatography medium using a 50-kDa-molecular-mass-cutoff Amicon Ultra-4 centrifugal filter (Millipore). Difference spectra were obtained by titrating affinity-purified ScErg11p6ϫHis and used to determine dissociation constant (K d ) values for the binding to the triazole drugs FLC and VCZ (30,31). Incremental additions of up to 7 l of triazole drug dissolved in dimethyl sulfoxide (DMSO) were added to a 0.5-ml sample of 1 M ScErg11p6ϫHis in affinity chromatography buffer in a 10-mm-pathlength cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of the efflux transporter genes CDR1, CDR2, and MDR1 is a common mechanism of drug resistance in this organism (10,17,26). Point mutations in the ERG11 gene result in reduced binding affinity of azoles to their target without precluding enzymatic function (31). In addition to point mutations, overexpression of ERG11 has also been shown to decrease fluconazole susceptibility.…”
mentioning
confidence: 99%